Sport, gender and mega-events - Dashper, Katherine (Emerald studies in sport and gender, 2021)
Sport mega-events are more than just large-scale gatherings and celebrations of human athletic achievement; they are also arenas through which groups and individuals perform, reinforce, challenge and disrupt identities, power and status. Understanding that sport is widely recognised as a practice through which normative ideas of gender are both reinforced and challenged, this book explores how this is magnified in the context of sport mega-events with their associated global media attention, elite performance, and social and cultural relevance. As sport mega-events become ever more prominent in popular culture, and are used by governments as tools to stimulate national and regional development, critical analysis of the gendered aspects of mega-events is increasingly important. Featuring a range of mega-event case studies and conceptual discussions, Sport, Gender and Mega-Events shows the significance of mega-events to wider sporting practices, and considers how these highly mediatised global phenomena both reflect and help shape broader ideas about gender, sex and identity in and beyond sport. Demonstrating how mega-events represent an important context through which to explore questions related to sex, gender and identity, Dashper's exquisitely collated chapters unpick mega-events as gendered entities and showcase how they both position athletes in relation to one of two binary sex positions - male or female - and also push the boundaries of what we see and accept as recognisably gendered male or female bodies and identities.